2005
DOI: 10.4269/ajtmh.2005.72.449
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Validity of the Buruli Ulcer Functional Limitation Score Questionnaire

Abstract: The reliability and validity of the earlier developed Buruli ulcer functional limitation score (BUFLS) questionnaire was assessed. Of 638 former Buruli ulcer patients (of 678 individuals examined), sufficient items on daily activities (>or= 13 of the 19) were applicable to calculate a score. To determine the validity, the functional limitation scores of the 638 individuals were compared with the global impression of the limitations, range of motion (ROM), and the social impact (change of occupation or educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2006
2006
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 15 publications
0
30
0
Order By: Relevance
“…Data on functional limitation was collected using the Buruli Ulcer Functional Limitation Score Questionnaire (BUFLSQ). Functional limitation was defined as impairment in carrying out daily activities as a result of BU [22,23]. Daily activities listed in the BUFLSQ irrelevant to a BU patient (either because the patient is too young or old to perform the task), was recorded as not applicable.…”
Section: Methodsmentioning
confidence: 99%
“…Data on functional limitation was collected using the Buruli Ulcer Functional Limitation Score Questionnaire (BUFLSQ). Functional limitation was defined as impairment in carrying out daily activities as a result of BU [22,23]. Daily activities listed in the BUFLSQ irrelevant to a BU patient (either because the patient is too young or old to perform the task), was recorded as not applicable.…”
Section: Methodsmentioning
confidence: 99%
“…The avoidance of aggressive surgical procedures produces more satisfactory functional results. 58 It has been observed that extensive and unnecessary surgeries can damage healthy tissues and do not prevent relapses. For patients with facial lesions, surgery is not a treatment option.…”
Section: Treatmentmentioning
confidence: 99%
“…Patients not treated early often suffer from functional disabilities in the long run, with joint movement impairment, which restricts their ability to execute and participate in daily activities. 5,6 Early diagnosis and a specific treatment for BU associated with interventions that prevent disabilities are crucial for satisfactory treatment results. 7,8 When necessary, surgery associated with antimicrobial therapy is the recommended treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Using this system, 362 (57%) of 638 patients in Benin and Ghana had persistent functional limitation after 4 years. 112 The average limitation score was variable with 31% in Benin and 15% in Ghana. The mean limitation score in 65 patients without visible contractures was 13%, whereas in 23 patients with visible contractures or an amputation it was >50%.…”
Section: Functional Limitationsmentioning
confidence: 99%
“…110 A BU functional limitation scoring system has been developed to assess the nature and severity of limitation, 111 which is helpful in clinical trials of treatment. 112 The BU functional limitation scoring system comprises a list of daily activities that were investigated in patients with BU in Benin and Ghana following treatment. Using this system, 362 (57%) of 638 patients in Benin and Ghana had persistent functional limitation after 4 years.…”
Section: Functional Limitationsmentioning
confidence: 99%